Employers' Demand for Personality Traits - Vera Brenčič; Andrew McGee (Institute of Labor Economics (IZA), 2023)
We measure firms' demand for workers' personality traits expressed in job ads and find that firms primarily demand workers who are extroverted, conscientious, and open-to-experience. The personality demand measures are correlated with the soft skills required on the job and produce intuitively plausible rankings of occupations in terms of personality requirements. Consistent with firms needing more time to fill vacancies with more requirements, ads requiring extroversion and conscientiousness remain posted online longer. Using the personality demand measures and wage information in the ads, we show theoretically and empirically that firms seeking conscientious workers are less likely to offer incentive pay.
Keywords: D22; J23; J24; J33; M51; 330; personality; job ads; method of pay